PENGARUH LITERASI KEUANGAN DAN PENDAPATAN PERKAPITA TERHADAP KONSUMSI RUMAH TANGGA DI INDONESIA: ANALISIS EKONOMI ISLAM - Abd Wahab; Aryadimas Suprayitno; Arva Athallah Susanto; Sulistya Rusgianto (Universitas Negeri Surabaya, 2025)
The decline in people's purchasing power and weakening household consumption growth in recent years pose serious challenges for the Indonesian economy. Financial literacy and income inequality are thought to be factors that influence people's consumption behavior. This study aims to analyze the effect of financial literacy and per capita income on household consumption in Indonesia from an Islamic economic perspective. A quantitative approach was used with panel data regression analysis through the Fixed Effect Estimated Generalized Least Squares (EGLS) model. The data used was secondary data from 34 provinces in Indonesia for the three periods of 2016, 2019, and 2022, sourced from the Financial Services Authority (OJK) and the Central Statistics Agency (BPS). The results of the study show that financial literacy and per capita income have a positive and significant effect on household consumption, which means that the higher the level of literacy and income, the greater the level of consumption. These findings emphasize the importance of improving financial literacy as an effort to strengthen household financial welfare. From an Islamic economic perspective, the results of this study emphasize the importance of fair, balanced, and socially oriented consumption behavior as a manifestation of the implementation of the maqashid sharia principle, which will encourage wiser and more sustainable household financial management.